Optimization of analog interface of information-measuring systems for remote measurement of mechanical quantities - Квасников, Владимир Павлович; Орнатский, Дмитрий Петрович; Осмоловский, Александр Иванович (Eastern-European Journal of Enterprise Technologies, 2014)
The error analysis of the analogue interface generalized structure with the standardized signal 4-20 mA is considered, the algorithms of calculating the filter parameter to prevent the effect of spectrum aliasing during input signal sampling are presented, and the reason of frequency of sampling and bitness of ADC (analog-digital converter) is given. The proposed method for optimizing the analogue information-measuring system interfaces for remote measurements allows more thoroughly consider the issues of accounting errors during designing information-measuring systems for mechanical quantities. Regulation and accounting of error features of the measuring systems IMS (information-measuring systems) has special peculiarities: it is better to prefer error regulation with separation into components, and also to regulate error features for stable service conditions taking into account metrological characteristics of a computing component. The analogue interface error classification and the main error structure is proposed, and also underlining the analogue interface in the measuring channel structure as the nexus between the sensor and data gathering system to satisfy all the demands. Such method allows taking into account all the analogue interface error components in better way and obtaining the computation correlation both for signals with continuous spectrum (in a root-mean-square metric) and for determinated signals (in a uniform metric) for antialiasing filter parameters.